Lanthanide‐Catalyzed Reversible Alkynyl Exchange by Carbon–Carbon Single‐Bond Cleavage Assisted by a Secondary Amino Group. Issue 38 (11th August 2016) - Shao, Yinlin; Zhang, Fangjun; Zhang, Jie; Zhou, Xigeng
Abstract: Lanthanide‐catalyzed alkynyl exchange through C−C single‐bond cleavage assisted by a secondary amino group is reported. A lanthanide amido complex is proposed as a key intermediate, which undergoes unprecedented reversible β‐alkynyl elimination followed by alkynyl exchange and imine reinsertion. The in situ homo‐ and cross‐dimerization of the liberated alkyne can serve as an additional driving force to shift the metathesis equilibrium to completion. This reaction is formally complementary to conventional alkyne metathesis and allows the selective transformation of internal propargylamines into those bearing different substituents on the alkyne terminus in moderate to excellent yields under operationally simple reaction conditions. Abstract : A good swap : Lanthanide‐catalyzed alkynyl exchange through C−C single‐bond cleavage enabled the selective transformation of internal propargylamines into differently substituted propargylamines in moderate to excellent yields. As an alternative to metathesis for the reconstruction of alkynes, this reaction has significant advantages, such as broad scope and excellent control of selectivity.